2004
DOI: 10.1534/genetics.166.3.1343
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Contributions of Dorsal Group and JAK-Stat92E Pathway Genes to Larval Hemocyte Concentration and the Egg Encapsulation Response in Drosophila

Abstract: Drosophila larvae defend themselves against parasitoid wasps by completely surrounding the egg with layers of specialized hemocytes called lamellocytes. Similar capsules of lamellocytes, called melanotic capsules, are also formed around "self" tissues in larvae carrying gain-of-function mutations in Toll and hopscotch. Constitutive differentiation of lamellocytes in larvae carrying these mutations is accompanied by high concentrations of plasmatocytes, the major hemocyte class in uninfected control larvae. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
143
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(161 citation statements)
references
References 43 publications
11
143
2
Order By: Relevance
“…They found that both the JAK/STAT and Toll pathways responded to parasitization. This corresponds with work showing that both the Drosophila JAK homolog Hop and the Toll pathway are required for a proper encapsulation response (27). It could be that these pathways are required for prohemocytes to react to some signal from activated circulating hemocytes.…”
Section: Encapsulationsupporting
confidence: 84%
See 2 more Smart Citations
“…They found that both the JAK/STAT and Toll pathways responded to parasitization. This corresponds with work showing that both the Drosophila JAK homolog Hop and the Toll pathway are required for a proper encapsulation response (27). It could be that these pathways are required for prohemocytes to react to some signal from activated circulating hemocytes.…”
Section: Encapsulationsupporting
confidence: 84%
“…1B). Yet, in hop loss-of-function larvae, the numbers of circulating hemocytes are comparable to wildtype larvae (26,27). Interestingly, Hop is required for the larvae FIGURE 1.…”
Section: Hemopoiesis and Cell Differentiationmentioning
confidence: 97%
See 1 more Smart Citation
“…They are considered essential for encapsulation and were long described as a plasmatocyte-derived form Rizki, 1980, 1984). Many studies established that plasmatocytes and lamellocytes follow specific differentiation pathways (Lanot et al, 2001;Sorrentino et al, 2002Sorrentino et al, , 2004Meister, 2004;Crozatier et al, 2004;Krzemień et al, 2007). However, recent works on Drosophila hemocytes lineage showed that plasmatocytes could indeed differentiate into lamellocytes (Honti et al, 2010;Avet-Rochex et al, 2010;Stofanko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many mutants show increased lamellocyte numbers and form melanotic masses, ''pseudotumors,'' in what is probably an overreaction of the cellular immune response (18,19). Notably, mutations that activate the Toll and Jak͞Stat pathways show this phenotype, suggesting an important role for these pathways in the cellular response (20)(21)(22)(23). Furthermore, Notch function is required for a normal cellular response (16).…”
mentioning
confidence: 99%